Transformation and regulation of nitrogen and sulfur during pyrolysis of oily sludge with N/S model compounds. (15th September 2022) - Li, Jiantao; Sun, Bingyan; Lin, Fawei; Tian, Wangyang; Yan, Beibei; Song, Yingjin; Chen, Guanyi; He, Chi
Highlights: PAM/SDS were stage pyrolyzed to investigate N/S transformation behaviors in oily sludge. Primary pyrolysis of PAM led to massive release of C6 H9 NO2, C5 H7 NO2 and NH3 . Low temperature pyrolysis of SDS led to intense SO2 emission. Dosing of Ca(OH)2 /Fe2 O3 was an effective regulatory strategy for N/S-pollutants. Abstract: Pyrolysis of oily sludge (OS) is an alternative for energy recovery with less pollutants. However, the migration of nitrogen and sulfur during pyrolysis process remain challenges for environmental concern and subsequent utilization of the recovered fuel. In this work, stage pyrolysis experiments of polyacrylamide (PAM) and sodium dodecyl sulfonate (SDS) under OS surroundings were conducted in a thermogravimetry-mass spectrometry-infrared spectroscopy and a fixed reactor to investigate the transformation behaviors of N/S-containing pollutants. Ca(OH)2 and Fe2 O3 were then used as inhibitors to regulate nitrogen and sulfur behaviors. Results showed that 3, 3 dimethylpyrrolidine-2, 5-dione (C6 H9 NO2 ), glutarimide (C5 H7 NO2 ) and NH3 were the primary N-containing pollutants in liquid and gaseous products, which were generated from PAM via deamination reactions at 200–400 °C. SO2 was the dominant S-containing pollutant, which was generated from SDS via desulfonation at temperature below 300 °C. The dosage of Ca(OH)2 catalyzed the deamination and cracking reactions, and thus led to more N/S-containing pollutants. Fe2 O3 suppressed the N/S-containing pollutants significantly because it could increase the energy barrier of N/S-containing pollutants and fix the released NH3 and SO2 into solid residues. This work facilitated the understanding of the nitrogen and sulfur transformation behaviors and would provide a possible regulatory strategy for clean fuel recovery.